Achievements and challenges of modified wood on the example of birch veneer - Shamaev Vladimir; Medvedev Ilya; Russu Aleksander; Tyurin Aleksander; Samodurov Aleksander; Yunak Maria; Storodubtseva Tamara; Ziemelis Andris; Garkusha Oksana (BIO Web of Conferences)
The article provides a comparative analysis of modern technologies for producing various grades of modified wood, such as Accoja, Kebony, Belmadur, Destam, Woodest, Thermowood and others. A brief description of new modification technologies developed at Voronezh State University of Forestry and Technologies is provided. The most promising of them are the following: technology of pressing and molding a cylindrical blank into timber, when the price of modified wood becomes less than the price of natural oak; technology for changing the strength, color and texture of wood to obtain complete analogues of polysander, mahogany, etc.; technology of wood pressing upto the density of wood substance; technology of plywood strengthening using nanocrystalline cellulose for LVL blocks production; manufacturing technology for power transmission poles and railway transfer bars due to the “self-pressing” effect; technology for producing railway ties, where the operations of drying, impregnation and pressing are combined in place and time. Production technology of end-panel parquet intended for use in gyms, supermarkets, universities, schools, etc. has been examined in detail, since wear resistance of end-face parquet is 3-4 times higher than that of natural oak one. A distinctive feature of the technology is that birch wood is pressed along the fibers.